Public attitudes towards gambling product harm and harm reduction strategies: An online study of 16-88 year olds in Victoria, Australia - Thomas, S.; Randle, M.; Bestman, A.; Pitt, H.; Bowe, S.; Cowlishaw, S.; Daube, Mike (BioMed Central, 2017)
Background: Gambling has quickly emerged as an important global public health issue. With new technologies used to develop high intensity gambling products and promotions aimed at driving consumption, public health organisations and researchers, community groups, and politicians have argued for a range of regulatory and education measures aimed at reducing gambling harm. However, there has been limited research seeking to understand community perceptions of the harms associated with gambling products and environments, and the level of community support for strategies designed to prevent and reduce gambling harm. Methods: An online study of 500 adolescents and adults (aged 16 and over) was conducted with a representative sample (by age and gender) of individuals who were current residents in the state of Victoria, Australia. Participants were asked a range of questions about their own gambling behaviours, with the Problem Gambling Severity Index (PGSI) used as a measure of problem gambling. Participants were asked about their perceptions of harms associated with electronic gambling machines (EGMs), sports betting, horse betting, and casino gambling. They were also asked about the extent to which they agreed or disagreed with gambling harm reduction strategies related to marketing and promotions, restrictions on gambling products and venues, and public education campaigns. Quantitative data were analysed using descriptive statistics and paired t tests, with thematic analysis used to interpret qualitative responses to open-ended questionnaire items. Results: More than one third (n = 201, 40.2%) of participants were at risk of experiencing some level of harm from gambling (PGSI = 1), with 83 participants (16.6%) recording scores that indicated problem gambling (PGSI = 8). One in five participants gambled on EGMs at least monthly (n = 100, 20.0%). Those who gambled on sports did so frequently, with nearly 1 in 5 gambling on sport at least once a month (n = 87, 17.4%). Over half of the sample rated casino gambling and EGMs as very harmful, while one third rated these forms of gambling as extremely harmful. Over one third of the sample rated horse and sports betting as very harmful, with one in five rating these products as extremely harmful. There was strong agreement with the need to ban gambling advertising during children's viewing hours, during sporting matches and at sporting venues. The majority of participants agreed with reducing and restricting EGMs, and providing more public education for both adults and children about the negative consequences from gambling. Conclusions: The findings suggest a strong perception in the Victorian community that gambling products are harmful. While governments have been reluctant to implement a comprehensive approach to reducing gambling harm, this study reveals significant community support for a range of harm reduction and prevention measures associated with gambling products. Public health practitioners can use this evidence in advocating for a comprehensive public health approach to reducing the harms associated with gambling promotions and products.